THE ROLE OF SELLING EXPERIENCE IN INCREASING SALESFORCE PERFORMANCE - Sri Purwantini; Endang Rusdianti; Paulus Wardoyo (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
Rural Bank (RB) is a company that functions as an intermediary institution. NPL is a measure of Rural Bank performance. Currently, the NPL of Rural Bank headquartered in the city of Semarang has an average level of above 5%. Previous research has shown controversy over the results of research on adaptive sales behavior to Salesforce performance. Likewise, the effect of customer orientation on Salesforce performance. Based on the phenomenon and the controversy of the research results, this provides an opportunity to conduct further research.This research will be conducted at Rural Bank that have a Head Office in Semarang City, currently totaling 22 conventional Rural Bank. Meanwhile, the research unit is sales personnel or what is commonly referred to as Salesforces at the Rural Bank and the number is unknown. The results of this study are expected to contribute to the development of science, especially marketing management.